(untitled) (Academicia Globe: Inderscience Research, 2022)
This article implements a philosophical understanding of the concept of the game. The classification of a game phenomenon with a multi-valued value is presented. The scientific and theoretical interpretations of the game are critically analyzed, and at the same time, on the basis of their acceptance of the heuristic side, a philosophical definition of the game is presented.